Roles of platelet factor 4 in hematopoiesis and angiogenesis - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2006)
Platelet factor 4 (PF4) has been recognized as a physiological inhibitor of megakaryocytopoiesis and angiogenesis for two decades. Structure-function studies have shown that the DLQ determinant in position 54-56 is necessary for megakaryocytic inhibition whereas mutations of these residues into ELR sequence and more importantly, into DLR sequence, induce a stronger inhibitory activity of peptide p47-70 on angiogenesis. The (x-helix region of peptides may participate in the fixation of the effector to its cellular receptor and the other important structural domains would activate the receptor. In vivo, PF4 and its related peptides can protect hematopoiesis from chemotherapy by enhancing cell viability and suppress tumor growth through anti-angiogenic pathway. Several PF4 fragments and modified molecules exhibit antiangiogenesis properties and may become an alternative for further therapeutic angiogenesis.
Keywords: platelet factor 4; megakaryocytopoiesis; hematopoiesis; angiogenesis; stem cells; PLATELET FACTOR-IV; FIBROBLAST-GROWTH-FACTOR; ENDOTHELIAL-CELL PROLIFERATION; MEGAKARYOCYTOPOIESIS IN-VITRO; AMINO-ACID SEQUENCE; C-MPL LIGAND; CXC CHEMOKINES; MURINE MEGAKARYOCYTOPOIESIS; INHIBITS ANGIOGENESIS; RECEPTOR DIMERIZATION